The Determinant of Credit Fund Disbursement of Pawnshop Company in Central Java Province - Norma Yuristiana (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2017)
Pawnshops as nonbank financial institutions whose core business is credit fund distribution services to the public on the legal basis is recomended to pay the company's investment, consumption activities, as well as the activities of the distribution of goods and services. This study aims to analyze how much influence the gross domestic regional product, unemployment, and inflation rates against the disbursement of credit at Central Java Pawnshops. This study uses secondary data from the Central Statistics Agency of Central Java province from 1984 to 2013. The variables of this study gross domestic regional product, unemployment and inflation rates in Central Java. In this study, we used quantitative study methods by using multiple linear regression analysis with Ordinary Least Square method (OLS). The results of this study note that gross domestic regional product and a significant positive effect on the disbursement of credit, unemployment did not effect the disbursement of credit, and inflation rates positive and significant impact on the distribution of credit funds. Variables gross domestic regional product, unemployment, and inflation together effect the disbursement of credit funds pawnshops in Central Java as for its influence positively and significantly